Musykillāt at tallāmiiż fi mahārāt al kitābiyyat lita’liim al lugat al ‘arabiyyat bi madrasat mutawasitat Ṭariiqa al jannat bandung - Althoof, Sayyid (Universitas Islam Negeri Imam bonjol Padang, 2024)
This research aims to demonstrate the issues of students' writing skills in learning Arabic at Thariiqul Jannah Junior High School in Bandung. This study uses qualitative research methods with a phenomenological approach model by Stevick, Colaizzi, and Keen. Data collection techniques include in-depth interviews with research subjects, participant observation, and document tracing. It was found that there are several issues with students' writing skills, including: (1) Issues in transferring words, sentences, or texts (dictated transcription and visual transcription), (2) Issues in composing words, sentences, or texts from sounds (auditory transcription), (3) Issues in writing answers to orally posed questions (examination dictation), (4) Issues in arranging words into sentences, (5) Arranging words into paragraphs (directed composition), (6) Issues in writing free compositions (free composition). From this research, it is hoped that all forms of issues related to writing skills can become a needs analysis material for educators to improve quality, as well as a literacy study and reference for researchers focused on this theme.